AMMONICAL - NITROGEN REMOVAL BY AN AEROBIC HETEROTROPHIC BACTERIUM, Microbacterium sp., VCM11 - S., Muthukrishnan,; V., Sabaratnam,; Chong, V.C. (Malaysian Journal of Science, 2012)
Bacterial strains were isolated from shrimp culture wastewater and assessed for ammonia reduction activity. Nine strains were selected based on nitrate reduction test. Out of nine strains, VCM11 showed significant (p ≤0.05) ammonical-nitrogen (AN) removal compared to control. Based on biochemical tests, the strain was identified as Microbacterium sp. Strain VCM11 was inhibited in all the antibiotic tests (troleandomycin, rifamycin SV, lincomycin, and nalidixic acid). Different parameters including sodium chloride (NaCl) concentration and temperatures were tested. The results obtained indicated that VCM11 at 180rpm, 30°C, and 35 ppt of sodium chloride (NaCl) reduced 53.57 ± 3.16 NH3+- N to 4.83 ± 1.12 NH3+-N (90.98%) within 120 hours. (Keywords: water quality, ammonia content (AC), Microbacterium sp., biochemical tests and antibiotic tests)